O papel do ensino informal de ciências: uma análise sobre o impacto do show de energia sobre o interesse dos alunos para cursos das áreas de ciências exatas - Monteiro, Isabel Cristina de Castro [UNESP]; Sena, Galeno José de [UNESP]; Amorim, Carlos Eduardo Silva [UNESP]; Monteiro, Marco Aurélio Alvarenga [UNESP] (My University, 2012)
Our work aims to discuss the teaching of science in the context of informal education. Thus, we present and analyze the results of an initiative that we have made seeking to interest high school students to study sciences and technology. The Energy shows are activities which are presented in experimental demonstrations of science concepts to middle school students. After the show the students respond to a questionnaire which formed the basis for this study. The results indicate that the achievement of shows have had an impact on students.

Nosso trabalho tem por objetivo discutir o ensino de ciências no contexto da educação informal. Assim, apresentamos e analisamos os resultados de uma iniciativa que temos realizado buscando despertar o interesse de alunos do ensino médio para o estudo das ciências exatas e tecnológicas. Os shows de Energia são atividades nas quais são apresentadas demonstrações experimentais de conceitos científicos para alunos do ensino médio. Após a realização de cada show os alunos respondem a um questionário que serviu de base para a realização desse estudo. Os resultados obtidos indicam que a realização dos shows tem tido grande impacto sobre os estudantes.
The role of informal science education: an analysis of the impact of the energy show on the interest of students for courses in the fields of earth sciences
Keywords: Science education; Informal education; Education; Exact sciences; Atividade experimental; Divulgação científica; Ensino de Física